Bidirectional 4-PAM to Double Per-Fiber Capacity in 2-km Intra-Datacenter Links - Dario Pilori; Luca Bertignono; Antonino Nespola; Fabrizio Forghieri; Marco Mazzini; Roberto Gaudino (IEEE Photonics Journal, 2018)
This paper presents an experimental demonstration of bidirectional 4-PAM transmission for intra-datacenter links using a pair of SMF fibers. In the proposed architecture, each transceiver laser feeds both fibers, which are thus used bidirectionally to double the capacity per used fiber, wavelength, and laser. Besides the experimental demonstration, we also report a theoretical and simulative investigation on the penalty induced in this architecture by spurious connector back-reflections. We show that the resulting penalty can be kept under control for typical realistic connector reflection values, provided that each pair of lasers in both directions are separated by at least twice the system symbol rate.